Submandibular Dermatofibrosarcoma Protuberans: A Rare Case Report - Shimada, Akio; Wada, Kota; Fujikawa, Momoki; Yui, Ryosuke; Kato, Takakuni (JIBI INKOKA TEMBO, 2024)
Dermatofibrosarcoma protuberans (DFSP) is a rare, malignant, soft tissue tumor that originates in the skin and is encountered infrequently by otolaryngologists. In this study, we present a case of DFSP arising in the submandibular region.Our patient was a 26-year-old male who presented to our hospital with a cervical mass that he had been aware of for three months. Preoperative cytological diagnosis was not established through puncture cytology, and tumor resection was performed for both diagnostic and therapeutic purposes.Computed Tomography (CT) examination showed a solitary subcutaneous nodule with a contrast enhancement effect. Upon histopathological examination of the excised tissue, characteristic findings emerged. Spindle-shaped fibroblasts formed a distinctive floral structure, which is a hallmark of DFSP. Immunostaining further confirmed the diagnosis by detecting CD34 as a specific marker. The preferred treatment for DFSP is surgical resection, aimed at complete tumor removal with clear margins. Radiation therapy may be considered for unresectable cases, and there have been reports of molecular-targeted therapy effectively managing distant metastases. The prognosis is relatively good, with distant metastases occurring in only about 1% of cases, but local recurrence is frequent. As there have been reports of local recurrence after more than five years, long-term observation is necessary in this case as well.